2012
DOI: 10.1128/jcm.00420-12
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Mass Spectrometry in Today's and Tomorrow's Clinical Microbiology Laboratories

Abstract: bClinical microbiology is a conservative laboratory exercise where base technologies introduced in the 19th century remained essentially unaltered. High-tech mass spectrometry (MS) has changed that. Within a few years following its adaptation to microbiological diagnostics, MS has been introduced, embraced, and broadly accepted by clinical microbiology laboratories throughout the world as an innovative tool for definitive bacterial species identification. Herein, we review the current state of the art with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 34 publications
2
55
0
1
Order By: Relevance
“…T he introduction of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) in the clinical microbiology laboratories is changing the approach to bacterial and fungal identification (1)(2)(3)(4). In particular, several studies have already demonstrated the reliability of MALDI-TOF MS in the rapid identification of yeasts in different clinical settings (5-7), evidencing its cost-effectiveness in allowing the initiation of species-targeted antifungal therapy (7)(8)(9).…”
mentioning
confidence: 99%
“…T he introduction of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) in the clinical microbiology laboratories is changing the approach to bacterial and fungal identification (1)(2)(3)(4). In particular, several studies have already demonstrated the reliability of MALDI-TOF MS in the rapid identification of yeasts in different clinical settings (5-7), evidencing its cost-effectiveness in allowing the initiation of species-targeted antifungal therapy (7)(8)(9).…”
mentioning
confidence: 99%
“…Discriminatory peaks have been detected suggesting a direct link between infectious-related protease activity and a sepsis-specific diagnostic pattern for discrimination of patients with SIRS [30] . An interesting example is represented by the detection of the staphylococcal delta-toxin which was found associated with the acute infection [31] .…”
Section: Detection Of Virulence Factorsmentioning
confidence: 99%
“…The LC-ESI-QqQ in selected or multiple reactions way has been used for routine detection of small molecules including metabolites and drugs [31] . More recently, the LC-ESI-QqQ has been suggested as a replacement for classical ELISAs for the quantitation of proteins in complex matrices [98] .…”
Section: Other Technologiesmentioning
confidence: 99%
“…Our isolate could not be identified beyond the genus level using this approach since no SuperSpectrum specific for P. glucanolyticus was, at the time, included in the RUO database. With the Vitek MS IVD system, the isolate was also only identified to the genus level using the Advanced Spectra Classifier approach, which represents an extension of the SuperSpectrum approach (28). Our isolate could be identified beyond the genus level with the Bruker Biotyper system and the Vitek MS RUO system when the compare mode was used.…”
mentioning
confidence: 99%
“…The two major commercial MALDI-TOF MS systems are the Bruker Biotyper and the bioMérieux Vitek MS systems (28). The databases of both systems contain mass spectra of P. glucanolyticus.…”
mentioning
confidence: 99%